Metabolomic study of carotid–femoral pulse-wave velocity in women. Issue 4 (April 2015) - Menni, Cristina; Mangino, Massimo; Cecelja, Marina; Psatha, Maria; Brosnan, Mary J.; Trimmer, Jeff; Mohney, Robert P.; Chowienczyk, Phil; Padmanabhan, Sandosh; Spector, Tim D.; Valdes, Ana M.
<x xml:space="preserve">Abstract</x> Objective: Carotid–femoral pulse-wave velocity (PWV) is a measure of aortic stiffness that is strongly associated with increased risk of cardiovascular morbidity and mortality. The aim of the current study was to identify the molecular markers and the pathways involved in differences in PWV in women, in order to further understand the regulation of arterial stiffening. Methods: A total of 280 known metabolites were measured in 1797 female twins (age range: 18–84 years) not on any antihypertensive medication. Metabolites associated with PWV (after adjustment for age, BMI, metabolite batch, and family relatedness) were entered into a backward linear regression. Transcriptomic analyses were further performed on the top compounds identified. Results: Twelve metabolites were associated with PWV (P < 1.8 × 10−4). One of the most strongly associated metabolites was uridine, which was not associated with blood pressure (BP) and traditional risk factors but correlated significantly with the gene-expression levels of the purinergic receptor P2RY2 (Beta = −0.010, SE = 0.003, P = 0.007), suggesting that it may play a role in regulating endothelial nitric oxide synthase phosphorylation. On the other hand, phenylacetylglutamine was strongly associated with both PWV and BP. Conclusion: Circulating levels of uridine, phenylacetylglutamine, and serine appear strongly correlated with PWV in women.